2012
DOI: 10.15376/biores.7.4.5152-5166
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Cellulosic Waste Sawdust Into Reducing Sugars Using Mercerization and Etherification

Abstract: Pretreatment of sawdust using a combination of sodium hydroxide (NaOH) and monochloroacetic acid (MCA) was investigated for the formation of reducing sugars. Optimum conditions for the pretreatment process were determined by the amount of reducing sugars formed during the enzymatic hydrolysis of the pretreated substrate. It was found that mercerization by NaOH played an important role in increasing the degree of substitution (DS) and that the maximum solubility was achieved during the etherification by MCA. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…This could be due to the deacetylation of sawdust in alkali media [46][47][48] resulting in formation organic salts [47,49]. For example, Of et al [50] suggested cellulosate is an intermediate compound formed from cellulose in alkali medium through carboxymethyl process at low temperature at 70 °C. In the given work the oven curing at 70 °C, the appearance of the band near 895 cm −1 (Fig.…”
Section: Mineral Phasesmentioning
confidence: 99%
“…This could be due to the deacetylation of sawdust in alkali media [46][47][48] resulting in formation organic salts [47,49]. For example, Of et al [50] suggested cellulosate is an intermediate compound formed from cellulose in alkali medium through carboxymethyl process at low temperature at 70 °C. In the given work the oven curing at 70 °C, the appearance of the band near 895 cm −1 (Fig.…”
Section: Mineral Phasesmentioning
confidence: 99%
“…Serbuk gergaji kayu merupakan bahan lignoselulosa yang memiliki kandungan selulosa dan lignin yang besar. Untuk meningkatkan proses hidrolisis secara enzimatik maka perlu dilakukan perlakuan awal yang disebut proses delignifikasi dengan menggunakan bantuan senyawa katalis, salah satu caranya adalah dengan menggunakan katalis kimia berupa senyawa NaOH [21,22]. Berdasarkan Tabel 1, serbuk gergaji yang telah melalui proses delignifikasi dengan NaOH memiliki kadar selulosa yang lebih tinggi.…”
Section: Pembahasanunclassified
“…Saw dust is a polycrystalline structure materials, which contain crystalline cellulose and amorphous lignin region ( Kim et al 2012 ). The XRD pattern of t-SD-g-AAc is shown in the Fig.…”
Section: Resultsmentioning
confidence: 99%